Environmental performance : does corporate governance matter? - Romlah Jaffar; Razieh Adinehzadeh; Zaleha Abdul Shukor; Mara Ridhuan Che Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2018)
Corporate environmental management and performance have become increasingly significant for companies in recent years, as they should operate in line with societal values and norms. Top management of companies, which include their board members, have an important role to play to address environmental issues, which include compliance with environmental laws and regulations. However, despite the growing number of environmental problems, stakeholder pressures and media attentions, there are relatively few studies that consider the role of corporate governance mechanisms in influencing the corporate environmental performance. This study investigates this phenomenon built upon the stakeholder theory. The study employs a matched pairs’ design method to select sample of this study; compliant and non-compliant groups of companies listed on Bursa Malaysia for the year of 2013. Data for environmental performance (EP) information were obtained from the Malaysia Department of the Environment (DOE). Data for corporate governance were collected from annual reports of sample companies to form corporate governance index. Results show that corporate governance mechanism is positively associated with the environmental performance of companies in Malaysia. Results suggest that the existence of good corporate governance would lead to higher companies’ compliance with environmental regulations that positively affects environmental performance. Additional analysis, which uses an alternative measurement for corporate governance and environmental performance measures, also confirm this finding. The results of this study highlight the importance of corporate governance mechanism in the formulation of strategic direction and operational implementation especially in the area of environmental management to meet regulatory standards and stakeholders’ expectation.